2023
DOI: 10.3892/mco.2023.2627
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in malignant peritoneal mesothelioma (Review)

Abstract: Over the last decade, there has been a movement in cancer treatment away from cytotoxic therapies toward strategies that enhance the immune system against cancer. Immune checkpoint inhibitors (ICIs) have been incorporated into the treatment regimens for patients with various solid tumors. Mesothelioma trials revealed encouraging efficacy; however, patients with peritoneal mesothelioma are usually excluded, slowing the progress of improving the treatment of this aggressive cancer and compelling oncologist to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 82 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…However, the majority of MPeM cases are epithelial. Hence, these immunological and molecular differences between pleural and peritoneal mesothelioma hinder the extrapolation of any relevant findings [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority of MPeM cases are epithelial. Hence, these immunological and molecular differences between pleural and peritoneal mesothelioma hinder the extrapolation of any relevant findings [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The response rate was reported to be 16% in epithelioid, and it was noted that PDL1 expression was more common in the peritoneal subset with 25% of MPeM classified as having a tumor proportion score (TPS) greater than or equal to 50%. However, whether PDL1 expression is predictive of benefit remains unknown [5][6][7]. In another study, the clinical efficacy of immunotherapy in patients with advanced MPeM was evaluated, and an overall response rate of 19.2% and a median progression-free survival (PFS) of 5.5 months was reported [8].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most recent studies of immunotherapy in MPM was published in 2023, which reviewed the use of single or dual-agent immunotherapy or immunotherapy combined with chemotherapy. The authors concluded that due to the small number of patients with MPM in the clinical trials performed to date, no definitive conclusions could be reached, and therefore, no firm recommendations were made [85]. The authors proposed that given the lack of clear evidence regarding immune checkpoint inhibitors in comparison to chemotherapy as a first-line therapeutic choice for MPM, it would be reasonable to reserve them for use as a later option [85].…”
Section: Novel Therapiesmentioning
confidence: 99%
“…The authors concluded that due to the small number of patients with MPM in the clinical trials performed to date, no definitive conclusions could be reached, and therefore, no firm recommendations were made [85]. The authors proposed that given the lack of clear evidence regarding immune checkpoint inhibitors in comparison to chemotherapy as a first-line therapeutic choice for MPM, it would be reasonable to reserve them for use as a later option [85]. The use and outcome of molecular and immune therapy in MPM remain vastly unknown and are an extremely promising area of investigation for the future.…”
Section: Novel Therapiesmentioning
confidence: 99%
“…However, despite some studies reporting encouraging results, the efficacy of ICI in MPM has not been formally demonstrated due to the low number of MPM cases in clinical trials, which predominantly include MPlM. The molecular heterogeneity between MPM and MPlM also complicates the interpretation and extrapolation of results ( 1 , 2 , 6 , 7 ). Predictive biomarkers for response to immunotherapy in MPM are poorly defined.…”
Section: Introductionmentioning
confidence: 99%